Analyzing The Reluctance Of English As A Foreign Language Students To Engage In Spoken English Communication - Rejeki Sotani Zebua, Feliks (Jolly Journal of English Education, 2023)
This quantitative research study explores the factors contributing to English as a Foreign Language (EFL) students' fear of making mistakes when speaking English. The research involved 81 fifth-semester students from the English Education study program at Universitas Nias, who responded to a Likert scale-based questionnaire. The findings reveal that while a majority of students exhibit a neutral level of confidence and comfort when speaking English, they experience anxiety, worry, and embarrassment related to making mistakes. However, most students do not perceive making mistakes as a negative aspect of English language learning. Furthermore, they do not express significant concerns about being criticized or ridiculed by others. The study also highlights that students often strive for perfection when speaking English, putting pressure on themselves. These findings shed light on the complex interplay of emotions and perceptions in EFL students' language acquisition process. Understanding the factors influencing students' reluctance to speak English can inform educators and institutions in designing more supportive and effective language learning environments